Electrospun flexible nanofibers for electronic skin - Rajala, Aino (My University, 2025)
Electrospinning is a versatile method for producing flexible nanofibers. Electrospinning uses an electrostatic field generated between the needle and the collector to produce thin fibres of nanometre diameter. The properties, morphology and diameter of the fibres can be influenced by various process, solution and environmental parameters. In addition, several methods can be used to produce electrospun nanofibers, such as single-fluid electrospinning, multi-fluid electrospinning and wet electrospinning. Different methods can be used to achieve different structures and properties of nanofibers. Electrospun nanofibers can be used in biosensors due to their suitable properties. Sensors such as strain and pressure sensors can measure human movements by placing an electronic skin on top of the human skin.

Sähkökehräys on monipuolinen menetelmä tuottaa taipuisia nanokuituja. Sähkökehräyksessä käytetään neulan ja keräimen välille muodostuvaa sähköstaattista kenttään ohuiden halkaisijaltaan nanometrien mittaisten kuitujen tuottamiseen. Kuitujen ominaisuuksiin, morfologiaan ja halkaisijaan voidaan vaikuttaa erilaisilla prosessi-, liuos- ja ympäristöparametreillä. Lisäksi sähkökehrättyjen nanokuitujen tuottamiseen voidaan käyttää useita menetelmiä kuten yksinesteinen sähkökehräys, moninesteinen sähkökehräys ja märkä sähkökehräys. Erilaisilla menetelmillä voidaan saavuttaa erilaisia nanokuitujen rakenteita ja ominaisuuksia. Sähkökehrättyjä nanokuituja voidaan käyttää biosensoreissa johtuen niiden sopivista ominaisuuksista. Sensoreilla, kuten venymä- ja painesensorit, voidaan mitatta ihmisten liikkeitä asettamalla iholle elektroninen iho.
Keywords: electrospinning, flexible nanofibers, electronic skin